Intraoperative pectoral block versus thoracic paravertebral block for postoperative analgesia after breast cancer surgery: A randomized controlled trial. Issue 3 (10th May 2022) - Sagun, Aslinur; Rumeli, Sebnem; Ozdemir, Levent; Azizoglu, Mustafa; Berkesoglu, Mustafa; Mutlu, Veli
Abstract: Background and Methods: With the increasing rate of breast cancer surgery, the pain management of these patients gains importance. The aim of this study is to compare the ultrasound (US) guided thoracic paravertebral block (TPV) versus intraoperative pectoral nerve block (PECS) with a low volume local anaesthetic for postoperative analgesia after breast cancer surgery. A total of 41 patients underwent mastectomy and sentinel lymph node biopsy or modified radical mastectomy were included in this randomized controlled, single‐blinded trial. The patients were divided into two groups as PECS and TPV blocks. In the PECS group, 10 ml of 0.5% bupivacaine was administered to the fascial plane by the surgeon. In the TPV group, 25 ml of 0.25% bupivacaine at T3 level was administered by the anaesthetist under US‐guidance. Visual analogue scale (VAS) scores and additional analgesic requirements were recorded at postoperative 0, 6, 12, 24 and 48 h. Results: In the TPV group, mean VAS score (VAS0) was significantly lower ( p  ˂ 0.001). In other time periods, there was no significant difference between the groups. Conclusions: It was observed that intraoperative PECS block was as effective as TPV in providing postoperative analgesia and additional analgesic requirements were similar. This result suggests PECS block may be a good alternative to TPV.